Analysis Of The Calculation Of The Building Structure Of The Two-Story Mortuary Initiation Building Of Ngudi Waluyo Hospital With Sni 1726 Of 2019 And The Sap2000 Application - Nurjanah; M. Nadhir Fahmi (JOSAR (Journal of Students Academic Research), 2025)
Indonesia is a country vulnerable to earthquakes, including the Blitar district located in zone 3. In the world of civil engineering, various types of building structures such as moment carrier frames and slider carrier frameworks are designed to meet different needs. Concrete structures, rigid frames, and wall frames are important components in building design. The Indonesian National Standard 1726 of 2019 sets out the methodology of earthquake resilience planning. Through quantitative research with the help of SAP2000, the structural analysis of RSUD Ngudi Waluyo's body recovery building showed sufficient strength and stability of the building in the face of earthquake loads.